The Effect of Leverage and Profitability on Earnings Management with Company Size as A Moderating Variable - Vivi Nur Hidayah; Tumirin Tumirin (Cv. Syntax Corporation Indonesia, 2026)
Profit management is a strategy implemented by company managers through the selection of accounting policies to change the projected figures stated in the financial statements which aims to manipulate the presentation of profit information so that stakeholders (stakeholders) obtain inaccurate information about the company's actual financial performance and stability. The objective of this study is to determine the extent to which leverage and profitability influence earnings management and to determine the extent to which firm size moderates this relationship. This study employs a quantitative approach using secondary data from companies in the food and beverage subsector listed on the Indonesia Stock Exchange from 2020 to 2024. The method used is purposive sampling, yielding 137 data units that meet the established criteria. To test the hypotheses, various linear regression techniques and Moderated Regression Analysis (MRA) were employed. The results indicate that leverage does not have a significant impact, whereas profitability is found to have a significant influence on earnings management. Meanwhile, firm size is not found to act as a moderating variable